The Greenwood encyclopedia of homes through world history - Steele, James, 1943- (Greenwood Press, 2009)
The house, throughout history, in every place in the world, has been built to provide shelter from the elements. The dwellings that have resulted are as different as the people that have built them, the social norms that prevailed at the time and place in which they were built and the natural environment that they adapted to. Studying them now in a comprehensive way allows us to understand the social, political, economic and religious conditions that existed for their inhabitants. They are a three-dimensional record of culture. Twenty-four pages of color images, along with black and white imag.